Potentiometric and spectrophotometric determination of the stability constants of quercetin (3,3 ',4 ',5,7-pentahydroxyflavone) complexes with aluminium(III) and iron(II) - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2005)
In this study, the stability constants of the complexes of quercetin formed with aluminium(III) and iron(II) were determined potentiometrically by using the Calvin-Bjerrum and Irving Rossotti methods and spectrophotometrically. The evaluated protonation constants of the ligand were found: log K-1=9.63 +/- 0.11 and log K-2=8.32 +/- 013, at 25 degrees C. For the aluminium and iron complexes logarithms of the stability constants were found: for Al: log K-1=14.05 +/- 0.09, log K-2=10.02 +/- 0.12, and for Iron: log K-1=9.44 +/- 0.11, log K-2=3.86 +/- 0.08.
Keywords: quercetin; aluminium; iron; stability constant; potentiometri; spectrophotometri; PLASMA